G-ODE, an extension of the apache ODE for grid services - Nguyen, Binh Thanh; Nguyen, Duc Huu; Nguyen, Thuy Thanh (Journal of Computer Science and Cybernetics, 2012)
Grid services and workflows using BPEL have gained much interest in Grid computing recently as they allow useful structured tasks to be composed and invoked automatically within a Grid environment. With normal Web services (stateless ones), the composition and invocation can be done with BPEL and its engines such as ActiveBPEL and Apache ODE. However, the invocation of Grid services (stateful ones) presents a problem for BPEL and its engines because they lack features for supporting stateful services. In our previous work [1], this problem was deeply analysed and from that a clean solution was proposed allowing BPEL-ODE invocation of Grid services. This paper aims to combine the previous result with new complete implementation for the proposed solution. The meaning of our solution will be explained more clearly through a BPEL workflow example. Our implementation called G-ODE, is an extension of the ODE enabling both Web Services and Grid Services invocation.